2019
DOI: 10.1039/c9ob00070d
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of the collagen triple helix in a hydrophobic environment

Abstract: The collagen triple helix is better suited for octanol than for water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…12b After reporting a hydrophobic P II helix, our recent study on collagen mimicking peptides suggests a possibility for oligomeric P II assemblies in hydrophobic media. 70 Therefore, our discovery of the TM P II helix opens up an avenue for engineering entirely new types of de novo membrane-associated peptide structures, not present in nature but deliberately constructed under laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…12b After reporting a hydrophobic P II helix, our recent study on collagen mimicking peptides suggests a possibility for oligomeric P II assemblies in hydrophobic media. 70 Therefore, our discovery of the TM P II helix opens up an avenue for engineering entirely new types of de novo membrane-associated peptide structures, not present in nature but deliberately constructed under laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Modification of charged side chains with nonpolar moieties through esterification has been shown to increase cell permeability 21 . While N-acetylated polyproline has been shown to be somewhat soluble in octanol, modification of proline to an indole can also increase hydrophobicity of peptides by further burying the polar backbone and still allows helical conformation 22 , and that structural architectures like collagen can form in octanol with similar modification 23 demonstrating the ability of peptide derivatives to form both secondary and quaternary structures in nonpolar solvents. These findings suggest that biopolymer derivatives would likely be more successful than their water-evolved counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies used this destabilizing effect of co‐solvents or additives on the triple helix to develop a solvent‐switching protocol for targeting damaged collagen in histological samples with collagen hybridizing peptides [25] . Other solvents than water, for example, propane‐1,2‐diol and octan‐1‐ol stabilize CMP trimers to a significant extent [26–27] . Our group showed that a local hydrophobic environment created by lipidation stabilizes collagen triple helices in water [13,28] .…”
Section: Introductionmentioning
confidence: 93%